Can Grants to Consortia Spur Innovation and Science-Industry Collaboration? Regression-Discontinuity Evidence from Poland - Bruhn, Miriam (The World Bank, 2017)
This paper uses a regression discontinuity design to study the effect of Poland's In-Tech program on innovation activities. The analysis focuses on a component of the program that provides grants to projects that are carried out by consortia of firms and research entities. Data from a 2016 follow-up survey of applicants to the 2012 and 2013 calls for proposals show that In-Tech largely funds projects that would not otherwise get funded by other agencies or by the consortia themselves, increasing the probability of a project being completed by almost 60 percentage points. The results also show that the program leads to more science-industry collaboration, and increases the probability of applying for a patent related to the proposed project, as well as the probability of publishing a research paper related to the project. The analysis also finds early effects on commercialization of products related to the proposed project, although these products currently still make up a small share of firm's sales